Napływ bezpośrednich inwestycji zagranicznych do nowych krajów członkowskich Unii Europejskiej - Bernaś, Bogumił; Kowalik, Paweł (Foreign Direct Investment in New Members States of the European Union, 2007)
Foreign direct investment (FDI) has been seen as a crucial factor and catalyst in the transition to I market economies. This publication investigates the recent evolution of FDI inflows to New Member I States of the European Union, as well as their distribution by activity and by investor country.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1159, s. 23-36